NH4+ Deprotonation at Interfaces Induced Reversible H3O+/NH4+ Co‐insertion/Extraction. (21st February 2023) - Huang, Meng; He, Qiu; Wang, Junjun; Liu, Xiong; Xiong, Fangyu; Liu, Yu; Guo, Ruiting; Zhao, Yan; Yang, Jinlong; Mai, Liqiang
Abstract: Ion insertions always involve electrode‐electrolyte interface process, desolvation for instance, which determines the electrochemical kinetics. However, it′s still a challenge to achieve fast ion insertion and investigate ion transformation at interface. Herein, the interface deprotonation of NH4 + and the introduced dissociation of H2 O molecules to provide sufficient H3 O + to insert into materials′ structure for fast energy storages are revealed. Lewis acidic ion‐NH4 + can, on one hand provide H3 O + itself via deprotonation, and on the other hand hydrolyze with H2 O molecules to produce H3 O + . In situ attenuated total reflection‐Fourier transform infrared ray method probed the interface accumulation and deprotonation of NH4 +, and density functional theory calculations manifested that NH4 + tend to thermodynamically adsorb on the surface of monoclinic VO2, and deprotonate to provide H3 O + . In addition, the inserted NH4 + has a positive effect for stabilizing the VO2 (B) structure. Therefore, high specific capacity (>300 mAh g −1 ) and fast ionic insertion/extraction (<20 s) can be realized in VO2 (B) anode. This interface derivation proposes a new path for designing proton ion insertion/extraction in mild electrolyte. Abstract : Accumulation of NH4 + on the electrode‐electrolyte interface was probed by in situ ATR‐FTIR. The formed NH4 + ‐rich domain induces the formation of protons. Subsequently, proton co‐insertion into VO2 happens, which achieved fast ion storage (charge/discharge in <20 s) and high capacity (>300 mAh g −1 ), and was revealed by in situ XRD and DFT calculation.